Reading Rieder by Lamplight - Benczik, Vera (Hungarian Journal of English and American Studies, 2020)
Book review: Rieder, John. Science Fiction and the Mass Cultural Genre System. Middletown, CT: Wesleyan UP, 2017. 224 pages. ISBN 9780819577160. Pbk. 22.95.